The formation of the citizen as a product of the public university on neoliberal international time, in the city of Monterrey Nuevo Leon, Mexico - Leal Iga, Jorge (2021)
Due to the neoliberal international trend, the public higher educational institutions in the world have modified their actions in order to adapt themselves to the new ways stipulated by the international economic financing organizations, transforming the academic forming of what the public education in the world used to represent. This investigation tried to find out if the formation of the current public university students shows a tendency towards the individualistic profile that privileges the satisfaction of their personal interest before the interests of the community, which is characteristic of the neoliberal citizenship. There was a total participation of 379 people in two samples to achieve this objective, with which it was determined that although this neoliberal formation does not exist in a generalized way in the groups analyzed, there is indeed a particular tendency that was detected in certain profiles, as well as inconsistencies in the behavior of the profiles described.